Volume 1: Applied Mechanics; Automotive Systems; Biomedical Biotechnology Engineering; Computational Mechanics; Design; Digital 2014
DOI: 10.1115/esda2014-20439
|View full text |Cite
|
Sign up to set email alerts
|

In-Process Quality Characterization of Grinding Processes: A Sensor-Fusion Based Approach

Abstract: The quality assessment of manufacturing processes has been traditionally based on sample measures performed on the process output. This leads to the common “product-based Statistical Process Control (SPC)” framework. However, there are applications of actual industrial interest where post-process quality measurement procedures involve time-consuming inspections strongly related to the operator’s experience and/or based on expensive equipment. Cylindrical grinding of large rolls may be one of them. The assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The in‐process acquisition of sensor signals has particular industrial relevance because it allows the detection of undesired process phenomena that affect product quality and implementation of adaptive control actions. However, signal data might present a multimode pattern caused by frequent changes of the cutting parameters during each grinding cycle, and this situation makes chatter detection a troublesome task using traditional control charting methods. Despite of a body of literature devoted to the chatter detection problem, few automatic methods have been considered for actual industrial implementation.…”
Section: A Real Test Casementioning
confidence: 99%
See 1 more Smart Citation
“…The in‐process acquisition of sensor signals has particular industrial relevance because it allows the detection of undesired process phenomena that affect product quality and implementation of adaptive control actions. However, signal data might present a multimode pattern caused by frequent changes of the cutting parameters during each grinding cycle, and this situation makes chatter detection a troublesome task using traditional control charting methods. Despite of a body of literature devoted to the chatter detection problem, few automatic methods have been considered for actual industrial implementation.…”
Section: A Real Test Casementioning
confidence: 99%
“…The signal was processed online to compute two synthetic indices denoted by rms j and kurt j , j = 1, 2, …, which consist of the root mean square index of the vibration signal and the kurtosis of its time‐domain distribution within the j th time window. The rms index was chosen because it represents the most basic choice for vibration monitoring in industrial applications . Our previous experimental studies showed that use of the kurt index in combination with the rms index enhances the capability of chatter detection.The result is a bivariate quality characteristic { x j ∈ ℝ 2 , j = 1, 2, …}, where x j = [ rms j , kurt j ] T .…”
Section: A Real Test Casementioning
confidence: 99%